Electronic questionnaire / Por Lip Yee - Por, Lip Yee (2001)
This project aims to develop an E-Questionnaire for users through the web. Besides that, it will create awareness among users on the proper way of using password and more. E-Questionnaire System provides users information for example information about password usage. Moreover, this system provides an example for users as a guideline to answer questionnaire on web. Those questions inside E-Questionnaire's questionnaire are in both open ended and dosed format. Users can answer in Malay and English languages. E-Questionnaire does provide online submitting facility. After accumulating, reports can be generated by users. This application will be developed using the prototype model. The software that used to develop the E-Questionnaire System are Microsoft Visual Interdev, Internet Information Server 4.0 and Microsoft SQL Server. The server will run on Windows NT while the client will operate on any platform. The E-Questionnaire will be build using Active Server Page (ASP) technology. ASP provides the capability for the Web server to process application logic, then deliver standard HTML to the client browser. VBScript and JavaScript will be used together with HTML to develop the E-Questionnaire. The survey method is used to elicit user requirements from potential users. The system is able to perform data entry, modification & deletion of data. The system also has error detection, help facility, and email-sending facility. The system has some security features, efficiency in computer technology, expendability, friendly user interfaces and a reasonable response time. This application will be developed using top down modular approach.